PENGARUH PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO RS KOMPUTER MEDAN - Ginting, Samuel T.U.A; Keliat, Ezranto; Simanjuntak, Yuli R. (Politeknik Negeri Lhokseumawe, 2023)
The purpose of this study was to determine the effect of product, price, and service quality on consumer satisfaction at a computer hospital shop. Where the Independent Variables consist of Product (X1), Price (X2), and Service quality (X3), and the Dependent Variable Consumer Satisfaction (Y). The survey was distributed to 96 respondents using probability sampling technique with random sampling. Statistical Test using SPSS Version 22, by looking for the Instrument Validity Test where r-Count 0.202 r-Table then all Indicator Variables X and Y are declared Valid, and Reliability Test where the Cronbach Alpha Coefficient Value of Variables X and Y 0.6 then Variables said to be reliable. Data analysis uses descriptive where all X and Y variables are in the interval 3.41 – 4.2, so it is included in the agreed criteria. and Statistical Test through the Classical Assumption Test where the regression model does not show symptoms of multicollinearity in the multicollinearity test, the regression model does not show heteroscedasticity symptoms in the heteroscedasticity test, and the nomality test where the linear regression model has used normal distribution data. Multiple Linear Regression Analysis where the Coefficient of Multiple Determination (R2) is 0.560 indicating that the X variable simultaneously influences the Y variable by 56.0%. Partial Correlation where X1, X2, X3 have a significance of 0.000 0.005 that there is a significant correlation of the 3 variables, and the Partial Determination Correlation (r2) is the most dominant, i.e. Product is 0.497 or 49.7% the most dominant to the variable Consumer Satisfaction (Y) , Hypothesis test with F test where Sig F 0.000 0.005 then there is a joint effect of X1, X2, X3 on Y. and t test where variable X1 has a significant effect on Y, and variables X2, X3 each have no effect on variable Y Consumer Satisfaction.Keywords: Product, Price, Service Quality and Customer Satisfaction